2023
DOI: 10.1007/s40670-023-01727-w
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Impact of an Elective Research Experience on Medical Students’ Research Perceptions

Abstract: Introduction Physicians are at the centre of bench-to-bedside research, yet the number of physicians engaging in research is declining. One solution to overcome this alarming trend is exposing medical students to research. This study aims to assess the impact of engaging medical students in research, and the feasibility of conducting research solely using online communication. Methods A pilot elective research opportunity was offered to medical students enrolled to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…During block 1, participants will engage in activities either in a pre-selected preclinical, para-clinical, or other basic sciences laboratory, or work alongside a researcher involved in an ongoing research project and block 2 shall be done in a clinical department in the institution or as a supervised learning experience at a rural or urban community clinic. Previous studies have demonstrated that participation in an elective research experience has a positive impact across all personal and career characteristics (30). Furthermore, to promote research, the Indian council of medical research (ICMR) has introduced a short-term studentship program where undergraduates are encouraged to undertake research in their fields of interest by providing them with incentives and a certificate as a token of appreciation (31).…”
Section: Discussionmentioning
confidence: 99%
“…During block 1, participants will engage in activities either in a pre-selected preclinical, para-clinical, or other basic sciences laboratory, or work alongside a researcher involved in an ongoing research project and block 2 shall be done in a clinical department in the institution or as a supervised learning experience at a rural or urban community clinic. Previous studies have demonstrated that participation in an elective research experience has a positive impact across all personal and career characteristics (30). Furthermore, to promote research, the Indian council of medical research (ICMR) has introduced a short-term studentship program where undergraduates are encouraged to undertake research in their fields of interest by providing them with incentives and a certificate as a token of appreciation (31).…”
Section: Discussionmentioning
confidence: 99%
“…Iqra Nawaz, 1 Jonaviva Anthony Thomas, 2 Prakash Gupta, 3 Duha Shellah, 4 Mihnea-Alexandru Găman, 5 Juan C. Puyana, 6 Francisco J. Bonilla-Escobar. 7 Medical research serves as a pivot upon which the advancement of clinical practice oscillates.…”
Section: Should a Scientific Publication Be A Prerequisite To Graduat...mentioning
confidence: 99%
“…1,2 Research experiences improve students' comfort understanding research, increase their likelihood of conducting research in future, influence specialty choice, and increase odds of pursuing academic careers. [3][4][5][6] However, many African medical schools lack robust research training infrastructure and opportunities [7][8][9] , which can be associated with greater likelihood of research-inclined medical trainees emigrating to high-income countries. 10 The Sub-Saharan African Medical School Study (SSAMSS) of >100 African institutions found that <10% of faculty members at most schools were involved in sponsored research, limiting knowledge generation, impeding recruitment and retention of talented faculty members, and harming student training.…”
Section: Introductionmentioning
confidence: 99%